2019
DOI: 10.1177/0734371x19881681
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality, Leadership, and Inclusion: How Do Racially Underrepresented Women Fare in the Federal Government?

Abstract: Women continue to be underrepresented in leadership positions, but how does the intersectionality of being both a woman and from a racially underrepresented group influence leadership representation and inclusion in the U.S. federal government? This study answers the call of scholars to examine intersectionality that has received little attention in public administration despite the emphasis on representative bureaucracy and social equity. Drawing upon data from the Federal Employee Viewpoint Survey, we find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 80 publications
(147 reference statements)
6
34
0
Order By: Relevance
“…These findings persist despite the fact that nearly three-quarters of respondents, both Whites and people of color, reported working in workplaces with diversity and inclusion initiatives, leading the reports' author to conclude that nonprofits continue to perpetuate systemic "White advantage." Such findings dovetail with research that uses intersectionality as a lens to understand existing leadership disparities and the experiences of women of color in the federal government (Nelson & Piatak, 2019).…”
Section: The Human Services Leadership Deficit and Persistent Gender ...supporting
confidence: 59%
“…These findings persist despite the fact that nearly three-quarters of respondents, both Whites and people of color, reported working in workplaces with diversity and inclusion initiatives, leading the reports' author to conclude that nonprofits continue to perpetuate systemic "White advantage." Such findings dovetail with research that uses intersectionality as a lens to understand existing leadership disparities and the experiences of women of color in the federal government (Nelson & Piatak, 2019).…”
Section: The Human Services Leadership Deficit and Persistent Gender ...supporting
confidence: 59%
“…When leaders possess these characteristics, it enables employees to feel included in the team, lower individual boundaries aimed at separating them from one another, generate common interests, and relatability to each other (Mor Barak et al 2016). These inclusive leadership practices can foster trust, communication, and engagement among employees, enhancing perception of their workplace as fair, cooperative and empowering (Andrews and Ashworth 2014; Nelson and Piatak 2021).…”
Section: Diversity Management Inclusive Leadership Practices and Orga...mentioning
confidence: 99%
“…While there is increasing attention on inclusion and its positive impact on employees' perception of organizational policies and practices, the concept of inclusive leadership practices is relatively new in public administration research. Currently, literature is limited to general discussion and conceptualization of this concept (Bae et al 2017; Nelson and Piatak 2021; Ohemeng and McGrandle 2021; Roberson 2006; Shore et al 2011. 2018).…”
mentioning
confidence: 99%
“…Males, who comprise nearly three fourths of all federal employees at NIST, do not tend to seek advice from females. These trends are not unique to NIST-there is a whole body of work that has shown that females are often not sought for advice, and that this lack of inclusion has detrimental effects on the career prospects of females [34,69]. Interestingly, these facts and the dynamics that they precipitate do not impede females from seeking other females as part of their advice-seeking interactions.…”
Section: ______________________________________________________________________________________________________mentioning
confidence: 99%